Effectiveness of Business Communication in Improving Organizational Productivity in The Digital Era - Angga Aldi Saputra; Apriyanti, Apriyanti; Darsi Ahmada; Itsnaini Chusnul Khotimah (Penerbit dan Percetakan CV. Picmotiv, 2025)
Business communication plays a central role in supporting organizational productivity, especially in today’s fast-paced and competitive digital era. This study aims to analyze how effective business communication influences organizational productivity, with a focus on the role of digital technology, internal communication, and adaptive communication strategies. The method used is a literature review with a descriptive qualitative approach. The results show that effective communication, supported by digital technology, enhances collaboration, transparency, and faster decision-making, which ultimately has a positive impact on work productivity. Recommendations are offered for organizations to foster a culture of open communication and invest in training for digital communication skills.